Determining the value of compensation for expropriation for a land located in the coastal area of the South Pacific, based on the econometric method of valuation - Paniagua Molina, Javier (2018)
The expropriation process is founded in the law which allows the State to acquire land in the public interest for it to pay the right amount. There is an initial condition before the expropriation and a other one after that condition that is generated as a result of being forced expropriation and, hence necessary to have tools to measure the change of condition. The objective of this research is to determine the land value analyzed before the expropriation and as well as damage to the remnant of what was then the expropriation. The econometric method was used applied to the valuation of land, this is a mathematical model that explains the value of the land in terms of determinants for the environmental conditions surrounding attributes.